Democratic Parenting In Fostering Early Childhood Independence - Maharany, Anggieta Zuliza; Shofwan, Imam (Jurnal Penelitian Pendidikan, 2025)
Parenting style is a set of attitudes and practices applied to children to predict their future behavior. This study aims to describe the role of democratic parenting in shaping the independence if early childhood in PAUD Junior, West Ungaran, usibg a descrptive qualitative method. This study uses primary and secondary data sources. The research rechniques used are observation, interviews,and documentation. In this study, data validity was tested using triangulation techniques. The study shows that  democratic parenting greatly supports the growth of independence in young children. This parenting style creates a loving and open communication environment that supports children's emitional developnent, increases their self- confidence, and improves their ability to manage their emotions. Democratic parenting provides controlled freedom, allowing children to make simple decisions and explore their environment, which encourages the development of intellectual independence and critical thinking skills. The application of a rational reward and punishment system helps children understand the consequences of their actions and improves their social skills through interaction with their peers.